Implementasi Konseling Industri dalam Meningkatkan Kinerja Karyawan di PT. Arara Abadi Distrik Nilo - Azra, Muhammad Zein; Kurniawan, Dery (IAIN Kudus, 2021)
Implementation of Industrial Counseling in Improving Employee Performance at PT. Nilo District Immortal Arara. The purpose of this study is to further review the counseling practices in the industrial sector so that they can be relevant according to the theory that is used as a reference. Research on the implementation of industrial counseling in improving employee performance is carried out using a qualitative approach with the type of field research (field research) with data collection techniques using Interview, Observation and Documentation. The subjects of this study were employees and two counselors at PT. Arara Abadi, Nilo District, Pelalawan Regency. The results showed that employee counseling or industrial counseling itself (functions, objectives, approaches, impacts, and limitations), and the process of implementing employee counseling were divided into three stages, namely before counseling, during counseling, and after counseling.Keywords: Implementation, Industry Counseling, Employee Performance